Comparative analysis of bank stability in Indonesia: A non-parametric approach on different banking models - Abdul Karim, Norzitah; Syed Jaafar Alhabshi, Syed Musa; Kassim, Salina; Haron, Razali (Bank of Indonesia, 2018)
The present study, grounded in theory of financial intermediation, provides new empirical evidence on comparison of bank stability measures of Islamic banks, conventional banks and other models in Indonesia. Specifically, 72 conventional banks, 4 Islamic banks, 3 conventional banks with Islamic subsidiaries and 2 subsidiary Islamic banks in Indonesia are considered, focusing on the sample period of 1999-2015. The study adopts z-score as a measure of bank stability, while a non-parametric multiple comparison analysis was used to test the significance of the differences in the bank stability of the different bank models, namely Islamic banks, conventional banks, subsidiary Islamic banks and conventional banks with Islamic subsidiaries. The sample period is further divided into three sub-periods, namely before the global financial crisis (1990-2006), during the global financial crisis (2007-2009) and after the global financial crisis (2010-2015) so as to gain more detail findings on the impact of the global financial crisis on the banks' stability. The impact of local crisis periods (1999-2001) on bank stability of different bank models is also investigated. Findings of this study contribute towards extending the theory of financial intermediation through empirical works of stability of different banking models namely Islamic banks, conventional banks, subsidiary banks and conventional banks with Islamic subsidiaries.